2016
DOI: 10.1038/ejcn.2016.186
|View full text |Cite
|
Sign up to set email alerts
|

Lower thigh muscle mass is associated with all-cause and cardiovascular mortality in elderly hemodialysis patients

Abstract: Lower thigh muscle mass is significantly associated with all-cause and cardiovascular mortality in hemodialysis patients. Our findings indicate the importance of focusing on the muscle mass of lower extremities to predict the clinical outcomes of hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 35 publications
1
12
0
1
Order By: Relevance
“…The finding was inconsistent with a previous study with more than 4 years of follow-up which showed that lower thigh muscle mass associated with higher mortality in hemodialysis patients. [33] Another study elucidated the association between lean body mass and survival among patients undergoing hemodialysis in different race and ethnicity. [34] Low lean body mass also showed a strong association with a higher rate of hospitalization and mortality in hemodialysis patients in a long-term follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…The finding was inconsistent with a previous study with more than 4 years of follow-up which showed that lower thigh muscle mass associated with higher mortality in hemodialysis patients. [33] Another study elucidated the association between lean body mass and survival among patients undergoing hemodialysis in different race and ethnicity. [34] Low lean body mass also showed a strong association with a higher rate of hospitalization and mortality in hemodialysis patients in a long-term follow-up study.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging techniques, such as computerized tomography (CT) and magnetic resonance imaging (MRI) or dual‐energy x‐ray absorptiometry (DEXA), have higher degree of precision and accuracy, and are also considered gold standards in the clinical setting; however, their clinical applicability is low . Recently, lower thigh muscle mass assessed by CT has been associated with all‐cause and cardiovascular mortality in elderly patients on hemodialysis . The limitations of these highly reliable imaging techniques relate to their cost, radiation exposure, limited availability at the bedside, the need for highly skilled operators and, in the case of DEXA, the influence of the hydration status.…”
Section: Protein Energy Wasting and Nutritional Status Evaluation In mentioning
confidence: 97%
“…5 Recently, lower thigh muscle mass assessed by CT has been associated with all-cause and cardiovascular mortality in elderly patients on hemodialysis. 22 The limitations of these highly reliable imaging techniques relate to their cost, radiation exposure, limited availability at the bedside, the need for highly skilled operators and, in the case of DEXA, the influence of the hydration status.…”
Section: Nutritional Status Evaluation In Esrdmentioning
confidence: 99%
“…Often, they do not have clear signs of malnutrition/PEW according to the standard parameters, such as prealbumin or transferrin levels, and their albumin levels may be modulated more by type of dialysis than by other means. Yet, they have a severely reduced muscle mass, and this reduction is correlated with survival [81,[84][85][86][87]. However, it is not unusual to find that these thin, fragile patients have very high dialysis efficiency, often linked to their low BMI and volume distribution, whose dialysis prescription should probably be decreased rather than increased [29,30].…”
Section: From the "Skeleton Man" To The Obese Sarcopenic Patientmentioning
confidence: 99%
“…Often, they do not have clear signs of malnutrition/PEW according to the standard parameters, such as prealbumin or transferrin levels, and their albumin levels may be modulated more by type of dialysis than by other means. Yet, they have a severely reduced muscle mass, and this reduction is correlated with survival [81,[84][85][86][87].…”
Section: From the "Skeleton Man" To The Obese Sarcopenic Patientmentioning
confidence: 99%